2011
DOI: 10.1111/j.1600-0447.2011.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

A multinational study of mental disorders, marriage, and divorce

Abstract: Objective Estimate predictive associations of mental disorders with marriage and divorce in a cross-national sample. Method Population surveys of mental disorders included assessment of age at first marriage in 19 countries (n = 46 128) and age at first divorce in a subset of 12 countries (n = 30 729). Associations between mental disorders and subsequent marriage and divorce were estimated in discrete time survival models. Results Fourteen of 18 premarital mental disorders are associated with lower likelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 38 publications
10
113
0
3
Order By: Relevance
“…Parental divorce has been consistently shown in several studies to contribute to depression (Breslau et al, 2011;Bruce and Kim, 1992) and poor psychological well-being for divorced couples (Booth and Amato, 1991). Offspring of depressed parents are also more likely to experience depression themselves (Beardslee et al, 1998;Leib et al, 2002;Peisah et al, 2004;Skeer et al, 2009), which has been shown as a risk factor for using illegal drug use, including cannabis (Liang et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Parental divorce has been consistently shown in several studies to contribute to depression (Breslau et al, 2011;Bruce and Kim, 1992) and poor psychological well-being for divorced couples (Booth and Amato, 1991). Offspring of depressed parents are also more likely to experience depression themselves (Beardslee et al, 1998;Leib et al, 2002;Peisah et al, 2004;Skeer et al, 2009), which has been shown as a risk factor for using illegal drug use, including cannabis (Liang et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…A study which was done in Turkey reported that female patients with major psychiatric disorders lacked the necessary parenting skills to various extents and that they tended to rely on their close relatives and institutions for childrearing. This was significantly higher in the schizophrenic and the bipolar groups as compared to that in the control and depressive groups [13]. It is actually known that schizophrenia and bipolar disorder result in a loss of empathy, a difficulty in understanding and expressing feelings and in a lack of impulse control and cognitive functions, which are necessary skills for parenting [22].…”
Section: Family Planningmentioning
confidence: 86%
“…In their study, Dilbaz et al, reported that the percentage of marriages for schizophrenic women was less and that 86.7% of the patients were single, particularly those with an early onset of schizophrenia [12]. In her study, Pehlivan presented that in the major psychiatric disorders -particularly in schizophrenia-the rate of being single/ divorced/ separated was frequently high as compared to that in the normal population [13]. Similarly, Breslau et al reported that mental disorders were positively associated with divorce [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 34 Three hypotheses have been proposed to explain why people living in urban areas should have 35 higher levels of poor mental health: psychosocial stressors; concentrated disadvantage and; 36 selective migration (Berry, 2007). According to the psychosocial stressors theory, residents in more 37 urbanised areas have poorer mental health because they are exposed to a greater level of individual 38 stress including material disadvantage, unemployment and marital breakdown; all of which are 39 known to be associated with poor mental health (Backhans and Hemmingsson, 2012;Boyle et al, 40 2008;Breslau et al, 2011). The concentrated disadvantage theory posits that the density of urban 41 populations concentrates insults such as area disadvantage, social fragmentation and crime and 42 disorder, intensifying their effects and inflating pressures on mental health (Berry, 2007).…”
Section: Introductionmentioning
confidence: 99%